Analysis Of Marketing Strategies To Increase Sales At Sales Ambassador Store Businesses In Kepahiang - Amelia, Amelia; Sachanovrissa , Silke; Hardinata , Dodi (Jurnal Pusat Manajemen, 2024)
The purpose of this research is to determine the marketing strategy implemented by the Duta Sale Du Kepahiang store business to increase sales volume. The research method used in this research is qualitative by looking at the type and source of data, data collection methods such as observation of research objects, interviews, analytical methods and literature studies and also using analytical methods. To find out what the strategy is, SWOT analysis is used. From the SWOT results, it was found that the results of the respective EFAS (external factors) obtained a value, the opportunity value was 1.47 and the threat value was 0.64, which means that this business has greater opportunities than threats. The IFAS (internal factor) strength score was 1.66 and the weakness score was 0.86. That means the strengths in this business are greater than the weaknesses it has. From the results of the SWOT analysis, it was found that the Duta sale shop in Kepahiang has strengths and opportunities so that it can take advantage of existing opportunities. The strategy that must be implemented in this condition is to support aggressive policy growth.